THE EFFECT OF COMPENSATION AND WORK ENVIRONMENT TO EMPLOYEE PERFORMANCE OF PT ASS - Magito, Magito (Dinasti International Journal of Management Science, 2020)
This study is to determine the effect of compensation and work environment on employee performance. The object of this research is PT ASS, located in Central Jakarta. The entire population numbered 43 people and the number of samples used as respondents in this study was 43 people, the way to distribute questionnaires was using the Simple Random Sampling technique. The research instrument used as a measuring instrument in the form of a questionnaire with a Likert scale. The results of the questionnaire answers are then processed using SPSS 23 Software, the data analysis used is statistical analysis in the form of multiple linear regression tests. The results of this study indicate partially compensation variables on employee performance and influence partially with work environment variables and influence on employee performance, this will be evidenced by the results of the partial significance test (t-test).